Serratia marcescens PLR enhances lateral root formation through supplying PLR-derived auxin and enhancing auxin biosynthesis in Arabidopsis - Zhang, Chunlei (Journal of experimental botany, 2022)
© The Author(s) 2022. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.